An Analysis of Compliment Strategies, Structural Patterns, and Pragmatic Functions in Gen Z Social Media Interactions - Anindita, Maharani Laksmi; Ymaniyar, Nurul Apriani; Rahma, Nurul Na’imahtul (Universitas Negeri Semarang, 2025)
Due to exposure to social media and evolving spoken language, younger generations are highly likely to develop different structure of compliments. This study aims to analyze the compliments used by the younger generation, specifically Generation Z (Gen Z), in social media TikTok. This study focused on the compliments' strategy, structure, and function. This research is a qualitative study with descriptive-comparative analysis. Two different procedures were used to obtain the data on compliments, the first procedure is to observe the TikTok videos and comments under the “Gen-Z Compliments” trend and the second is through naturalistic observation of a wide range of TikTok videos during the last 3 months, from June to August 2025. Of the total of 43 compliments identified, compliments with indirect strategies are more favored by Generation Z. Syntactically, the most used patterns are patterns [I (like/love) you, (please) (neg [don’t + v + NP])] and [You ADJ, I’m VP [(Vcont + NP)/(PP)]]. The indirect compliments do not have a fixed syntactic pattern. However, two linguistic features are used: semantic shifts and hyperbole. The function of these compliments also focuses solely on expressing admiration and increasing solidarity.